2006
DOI: 10.1111/j.1365-2648.2006.03677.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond empathy: expanding expressions of caring

Abstract: In this paper, a model describing nurses’ responses to patients who are suffering is presented. The nurse's level of engagement with the patient is affected by whether the caregiver is focused on him‐/herself or on the sufferer (i.e. embodied with the patient) and whether the caregiver is responding reflexively or with a learned response. Four types of communication patterns are identified: engaged responses (first‐level) are used in a connected relationship; when the nurse responses reflexively and is focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 28 publications
4
83
0
7
Order By: Relevance
“…For example, a review of the nursing literature concluded that empathy has been conceptualized in five distinct categories: (a) a human trait; (b) a learned communication skill; (c) a communication process; (d) an act of caring; and (e) a reciprocal relationship developed over time [25]. Such variations highlight the complexity of emotion and emotion work in healthcare settings as professionals balance their intuitive human condition with their professional roles and organizational goals [26].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a review of the nursing literature concluded that empathy has been conceptualized in five distinct categories: (a) a human trait; (b) a learned communication skill; (c) a communication process; (d) an act of caring; and (e) a reciprocal relationship developed over time [25]. Such variations highlight the complexity of emotion and emotion work in healthcare settings as professionals balance their intuitive human condition with their professional roles and organizational goals [26].…”
Section: Resultsmentioning
confidence: 97%
“…Interpreters actively provide emotional support and minimize negative attitudes/emotions during medical encounters by noting the needs to bridge cultural differences, enhance provider-patient bonding, and ensure quality care [28,40,60,71]. A recent study found that nurses highly value interpreters' function as patient ally [72], which echoes with the general tasks of nurses in which they often help patients to voice their concerns, address their information needs, and provide emotional support [26,73].…”
Section: Empathy As Emotion Work In Healthcare Interpretingmentioning
confidence: 97%
“…Morse et al (2006) recommended an alternative communication model in the hierarchical structure. According to this model, in the first stage, the nurse has spontaneous and reflexive responses; however, in the second stage, the responses are learned and therefore can be controlled.…”
Section: Related Literature On Empathymentioning
confidence: 99%
“…However, in several studies, nursing education has been strongly criticized for producing nurses who have good technical skills, but lack communication skills, a caring philosophy, critical thinking and creativity (McGregor 2005;Smith 2007). The analysis of the reviewed literature indicates that the concept of empathy in nursing and teaching is seen as an intellectual process, which involves at least two people, who have the ability to understand and the capacity to communicate that understanding back to the receiver in a caring and nonjudgmental way, with the emphasis on building cognitive professional communication and critical thinking (Ancel 2006;Finn 2009;Gillespie and McFetridge 2006;Halpern 2009;Kunyk and Olson 2001;Kelly 2007;Mercer and Reynolds 2002;Reynolds and Scott 2000;Rogers 1975; Morse et al 2006;Williams and Stockley 2010).…”
Section: Introductionmentioning
confidence: 99%